Comparing the genetic typing methods for effective surveillance and rabies control in Georgia - Condori, Rene E.; Kartskhia, Natia; Avaliani, Lasha; Donduashvili, Marina; Elbakidze, Tinatin; Kapanadze, Ana; Pieracci, Emily G.; Maghlakelidze, Giorgi; Wadhwa, Ashutosh; Morgan, Clint N.; Reynolds, Mary; Li, Yu; et al. (Frontiers in Microbiology, 2023)
A full nucleoprotein gene sequencing of 68 isolates collected from Georgia rabies passive surveillance system between 2015 and 2016 identified 2 distinct dog rabies phylogroups, GEO_V1 and GEO_V2, and both belonged to the cosmopolitan dog clade. GEO_V1 was found throughout the country and was further divided into four sub-phylogroups that overlapped geographically; GEO_V2 was found in the southeast region and was closely related to dog rabies in Azerbaijan. A sequence analysis of the full N gene, partial nucleoprotein gene of N-terminal and C-terminal, and the amplicon sequences of pan-lyssavirus RT-qPCR LN34 showed that all four sequencing approaches provided clear genetic typing results of canine rabies and could further differentiate GEO_V1 and GEO_V2. The phylogenetic analysis results vary and were affected by the length of the sequences used. Amplicon sequencing of the LN34 assay positive samples provided a rapid and cost-effective way for rabies genetic typing, which is important to improving rabies surveillance and canine rabies eradication globally.